Development of a low cost microfluidic sensor for the direct determination of nitrate using chromotropic acid in natural waters. Issue 13 (18th June 2015) - Cogan, Deirdre; Fay, Cormac; Boyle, David; Osborne, Conor; Kent, Nigel; Cleary, John; Diamond, Dermot
Abstract : This study has demonstrated, for the first time, a microfluidic autonomous analyser for the direct determination of nitrate, incorporating a modified version of the chromotropic method resulting in a direct, quick, inexpensive and simple procedure to measure nitrate in situ . Abstract : Progress towards the development of a miniaturised microfluidic instrument for the direct measurement of nitrate in natural waters and wastewater using chromotropic acid is presented. For the first time, the chromotropic method for nitrate analysis has been transferred to a microfluidic chip configuration that can withstand the extremely acidic nature of the reagent within a field deployable platform. This simple method employs one reagent mixed in a 1 : 1 ratio with the sample to produce a yellow colour absorbing strongly at 430 nm. A stopped flow approach is used which, together with the very rapid kinetics and simple reagent stream, enables an uncomplicated microfluidic design and field deployable platform with a sample throughput of 9 samples per h, limits of detection of 0.70 mg L −1 NO3 − and 0.31 mg L −1 NO3 − for seawater samples, with a dynamic linear range from 0–80 mg L −1 NO3 − and long-term reagent stability of up to 6 months. Validation was achieved by analysing split water samples by the analyser and ion chromatography, resulting in an excellent correlation co-efficient of 0.9969. The fully integrated sensing platform consists of a sample inlet with filter, storage units for chromotropic reagent and standards for self-calibration, pumping system which controls the transport and mixing of the sample, a microfluidic mixing and detection chip, and waste storage, all contained within a ruggedized, waterproof housing. The optical detection system consists of a LED light source with a photodiode detector, which enables sensitive detection of the coloured complex formed. The low cost of the platform coupled with integrated wireless communication makes it an ideal platform for in situ environmental monitoring.